Correlation of Prenatal and Postnatal Diagnosis in Umbilical-Portal-Systemic Venous Shunts - Jimenez-Gomez, Javier; Güizzo, Javier Roberto; Betancourth Alvarenga, Josue; Santiago Martínez, Saioa; Gaspar Perez, Mireia; Pina Perez, Silvia; Beltrán, Viviana Patricia; Loverdos, Inés; Esteva Miró, Clara; Jimenez Arribas, Paula; Sanchez Vazquez, Begoña; San Vicente Vela, Begoña; Álvarez García, Natalia; Nuñez García, Bernardo (European Journal of Pediatric Surgery, 2023)
Introduction Umbilical-portal-systemic venous shunts (UPSVS) are rare anomalies in the development of the fetal venous system. There are several postnatal and prenatal classifications of hepatic venous anomalies but the link between them is missing. We aimed to review the prenatal to postnatal diagnosis correlation in UPSVS at our center.Methods It is a retrospective study of patients diagnosed with UPSVS between 2019 and 2021 at our institution. Demographic, obstetric, genetic, and neonatal data were reviewed with special focus on prenatal and postnatal ultrasounds.Results A total of seven patients were diagnosed with UPSVS at a median of 24 (20–34) weeks of gestational age. All patients were male and 62% were Caucasian. None of the patients had chromosomopathies or cardiac anomalies. One patient had renal ectopia, another one had a single umbilical artery, and a third one suffered from intrauterine growth retardation. An umbilico-systemic shunt (USS) was found in two patients and a ductus venosus-systemic shunt (DVSS) in the rest. Patients with USS were diagnosed postnatally with intrahepatic portosystemic shunts. One of the DVSS patients was transferred to another hospital and the other four had normal postnatal cardiac ultrasounds, with normal abdominal ultrasounds in two patients and lack of postnatally abdominal control in the other two. All babies were found to be doing well at a median follow-up of 1 month (0–24).Conclusion There is a knowledge gap in the natural history of UPSVS between fetal and neonatal life. Building bridges between prenatal and postnatal research is mandatory in order to understand these rare anomalies.
Keywords: congenital portosystemic shunt; umbilical-portal-systemic venous shunt; fetal venous anomalies